A volatilidade implícita como instrumento de previsão para volatilidade futura baseado no mercado de opções do Índice Bovespa - Borges Filho, João Uchôa (2020)
In this paper, we analyzed the capacity of the local market to predict the realized volatility based on the implied volatilities of the options listed on the Bovespa index for the period of one month and three months, where the liquidity in the local market is concentrated. To further support the study, we did the analysis of several option deltas, not just restricting ourselves to options in the money. In addition, we compared this forward-looking model of implied volatility, with statistical models such as EWMA and GARCH, which are based on past volatility, and see which is more robust. The results obtained point out that the implied volatility seems to be a good estimator for the future volatility and superior to the other models verified for the maturities of 30 and 90 days. The results remained consistent when we carried out the study for the different options deltas in the sample. The evidence for this dissertation is in line with the findings of Melo (2009) and Vicente and Guedes (2010), which, despite being studies based on local stock options, conclude that the implied volatility is a biased, but efficient estimator.